PENYIMPANGAN POLA ASUH ANAK PADA MASYARAKAT PESISIR DI DESA TEMBURUN KECAMATAN SIANTAN TIMUR KABUPATEN KEPULAUAN ANAMBAS - Ali Azid; Rahma Syafitri; Siti Arieta (LPPM STISIP Persada Bunda, 2023)
Basically every parent wants their child to be happy, in good health, and have good behavior. Parents also try their best to nurture and care for and guide their children to have better character, in this case parents also have their own way of educating their children so that their children do not fall into negative things by means of violence so that researchers are interested in researching problems in Temburun Village, East Siantan District, Anambas Islands Regency. The purpose of this study was to determine the treatment of parents in raising children, to determine the treatment of parents in providing education to children and to determine the effect of parenting deviations on children. This study uses a qualitative method with a descriptive approach. The technique in determining the informants used purposive sampling technique with a total of 10 informants obtained from the main informants, namely the Temburun Village community and elements of the government. This research uses role theory by Biddle Thomas. The findings of this study are 1). The existence of acts of violence is caused by parents who want their children to be children who are devoted to their parents and do not violate parental orders. 2). Acts of violence against children are caused by venting parents' frustration on other people. 3). There is a lack of public awareness of acts of violence against children. The conclusion is that there are still acts of violence against children in Temburun Village, East Siantan District, Anambas Islands Regency, such as hitting, snapping, confining, pinching, slapping, and stomping on children. With this incident, it is hoped that the Anambas Islands Regency government should pay more attention to children's development by providing counseling for parents on better children.